The Effect of Density-Dependent Phase on the Locust Gut Bacterial Composition - Lavy, Omer; Gophna, Uri; Gefen, Eran; Ayali, Amir (Frontiers in Microbiology, 2019)
The desert locust demonstrates density-dependent phase polyphenism: For extended periods it appears in a non-aggregating, non-migrating phenotype, known as the solitary phase. When circumstances change, solitary individuals may aggregate and transform to the gregarious phenotype, which have a strong propensity for generating large swarms. Previous reports have suggested a role for gut-bacteria derived volatiles in the swarming phenomenon, and suggested that locusts are capable of manipulating their gut microbiome according to their density-dependent phases. Here, we directly tested this hypothesis for the first time. Using locusts of both phases from well-controlled laboratory cultures as well as gregarious field-collected individuals; and high-throughput sequencing. We characterized the hindgut bacterial community composition in the two phases of the desert locust. Our findings demonstrate that laboratory-reared gregarious and solitary locusts maintain a stable core of Enterobacter. However, while different generations of gregarious locust experience shifts in their Enterobacter's relative abundance; the solitary locusts maintain a stable gut microbiome, highly similar to that of the field-collected locusts. Tentative phase differences in wild populations’ microbiome may thus be an indirect effect of environmental or other factors that push the swarming individuals to homogenous gut bacteria. We therefore conclude that there are phase-related differences in the population dynamics of the locust hindgut bacterial composition, but there is no intrinsic density-dependent mechanism directly affecting the gut microbiome.